Advantageous grain boundaries in iron pnictide superconductors - Katase, Takayoshi (Nature Pub. Group, 2011)
High critical temperature superconductors have zero power consumption and could be used to produce ideal electric power lines. The principal obstacle in fabricating superconducting wires and tapes is grain boundaries—the misalignment of crystalline orientations at grain boundaries, which is unavoidable for polycrystals, largely deteriorates critical current density. Here we report that high critical temperature iron pnictide superconductors have advantages over cuprates with respect to these grain boundary issues. The transport properties through well-defined bicrystal grain boundary junctions with various misorientation angles (θ(GB)) were systematically investigated for cobalt-doped BaFe(2)As(2) (BaFe(2)As(2):Co) epitaxial films fabricated on bicrystal substrates. The critical current density through bicrystal grain boundary (J(c)(BGB)) remained high (>1 MA cm(−2)) and nearly constant up to a critical angle θ(c) of ∼9°, which is substantially larger than the θ(c) of ∼5° for YBa(2)Cu(3)O(7–δ). Even at θ(GB)>θ(c), the decay of J(c)(BGB) was much slower than that of YBa(2)Cu(3)O(7–δ).